Contemporary Chinese Political Thought : Debates and Perspectives - Dallmayr, Fred R. (Fred Reinhard), 1928-; Zhao, Tingyang (Book collections on Project MUSE., 2012)
Westerners seem united in the belief that China has emerged as a major economic power and that this success will most likely continue indefinitely. But they are less certain about the future of China's political system. China's steps toward free market capitalism have led many outsiders to expect increased democratization and a more Western political system. The Chinese, however, have developed their own version of capitalism. Westerners view Chinese politics through the lens of their own ideologies, preventing them from understanding Chinese goals and policies.